2018
DOI: 10.1080/24749508.2018.1452482
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric based prioritization of watershed for groundwater potential of Mula river basin, Maharashtra, India

Abstract: Morphometric analysis gives a quantitative description of drainage basin. The main aim of the present study is to identify the morphometric parameters of a watershed of Mula River basin, Pune district of state Maharashtra, India, and to prioritize the sub-basin. The work outlines the significance of digital elevation model for assessment of drainage pattern and extraction of relative parameters. Basin has been divided into 5 sub-watershed namely SW1 to SW5. The stream order of watershed ranges from first to si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(57 citation statements)
references
References 32 publications
0
43
0
6
Order By: Relevance
“…Over recent years various researchers have used morphometric variables (i.e., linear, areal, and shape) to prioritize watersheds using the application of remote sensing (RS) and geographical information system (GIS) by ordinary methods [4][5][6][7][8][9][10][11][12][13]. For instance, Shrimali et al [4] applied the feasibility of RS and GIS techniques to contextually investigate the Sukhana lake catchment in the Shiwalik hills to prioritize the soil erosion zones.…”
Section: Introductionmentioning
confidence: 99%
“…Over recent years various researchers have used morphometric variables (i.e., linear, areal, and shape) to prioritize watersheds using the application of remote sensing (RS) and geographical information system (GIS) by ordinary methods [4][5][6][7][8][9][10][11][12][13]. For instance, Shrimali et al [4] applied the feasibility of RS and GIS techniques to contextually investigate the Sukhana lake catchment in the Shiwalik hills to prioritize the soil erosion zones.…”
Section: Introductionmentioning
confidence: 99%
“…The change in stream order suggests that streams flow from high altitude with less lithological variations. Rai et al (2014) and Choudhari et al (2018) notice that maximum stream order is found in first-order streams. Stream order is shown in Fig.…”
Section: Figmentioning
confidence: 98%
“…Dendrite to the sub-dendrite stream has been obtained for the proposed site. According to Choudhari et al (2018), dendritic drainage pattern shows homogeneous and uniform Barind Multipurpose Development Authority (BMDA).…”
Section: Basic Parametermentioning
confidence: 99%
See 2 more Smart Citations